Induction immunosuppression in kidney transplantation: Thymoglobulin® (a literature review) - A. V. Pinchuk (Трансплантология (Москва))
Rabbit anti-thymocyte immunoglobulin, Thymoglobulin, was first obtained over 25 years ago and currently it is the most widely used antilymphocytic immunoglobulin in solid organ transplantation. Thymoglobulin interacts with a broad range of surface antigens of T-lymphocytes, natural killer cells, B-lymphocytes and plasma cells, as well as, withadhesion molecules and chemokine receptors, which results in a prolonged lymphopenia. Randomized studies have shown the effect of thymoglobulin on the prevention of acute graft rejection in kidney transplant. Experimental and clinicalstudies suggest that the use of thymoglobulin can reduce the impact of ischemia-reperfusion injury, thus reducing the incidence of delayed graft function (DGF). These studies have also shown the thymoglobulin advantage associated with minimizing the immunosuppression: the discontinuation of corticosteroids and calcineurin inhibitors (CNI) and with the improvement of treatment effect in relation to the cardiovascular system and kidneys. Optimal cumulative dose of Thymoglobulin in induction therapy scheme makes 6–7.5 mg/kg, provided monitoring via serial blood laboratory testsis performed.Currently, the induction with Thymoglobulin proved to be indicated for high immunological risk patients (increased DGF risk), and also for maintenance of immunosuppression effect in the standard risk group of kidney recipients receiving treatment with low doses of steroids and the calcineurin inhibitors (CNI), or in the cases of their complete withdrawal